A Novel Metamaterial MIMO Antenna with High Isolation for WLAN Applications - Nguyen Khac Kiem; Huynh Nguyen Bao Phuong; Quang Ngoc Hieu; Dao Ngoc Chien (International Journal of Antennas and Propagation)
A compact 2×2 metamaterial-MIMO antenna for WLAN applications is presented in this paper. The MIMO antenna is designed by placing side by side two single metamaterial antennas which are constructed based on the modified composite right/left-handed (CRLH) model. By adding another left-handed inductor, the total left-handed inductor of the modified CRLH model is increased remarkably in comparison with that of conventional CRLH model. As a result, the proposed metamaterial antenna achieves 60% size reduction in comparison with the unloaded antenna. The MIMO antenna is electrically small (30 mm × 44 mm) with an edge-to-edge separation between two antennas of 0.06λ0 at 2.4 GHz. In order to reduce the mutual coupling of the antenna, a defected ground structure (DGS) is inserted to suppress the effect of surface current between elements of the proposed antenna. The final design of the MIMO antenna satisfies the return loss requirement of less than −10 dB in a bandwidth ranging from 2.38 GHz to 2.5 GHz, which entirely covers WLAN frequency band allocated from 2.4 GHz to 2.48 GHz. The antenna also shows a high isolation coefficient which is less than −35 dB over the operating frequency band. A good agreement between simulation and measurement is shown in this context.